The process and mechanisms of the capitalization of marine space in China: a case study of mariculture on Guanglu Island, Changhai County - Liu, Tianbao; Wang, Yun; Zhao, Shan; Xu, Pengrui (Frontiers in Marine Science, 2024)
The phenomenon of transforming natural marine space into proliferative capital holds global significance in modern modes of production. Under China's socialist market economy, the property rights system and resource allocation methods have created a unique approach to the capitalization of marine space. Drawing on concepts related to the capitalization of space and land, this paper develops the idea of the capitalization of marine space. It is a process where the right to use the sea area is transferred by the rights holders through methods such as transfer, lease, or shares and is ultimately put into production as a means of production to realize the creation of capital value and surplus value. Using the mariculture industry on Guanglu Island in Changhai County as a case, this analysis delves into the process and mechanisms of the capitalization of marine space in China, the world's leading mariculture nation, while considering the material agency of marine space. The research results show that: ①The specific realization process of marine space capitalization in the mariculture industry has gone through three stages: from natural marine space to marine space resources, from marine space resources to marine space assets, and the participation of marine space assets in creating value and surplus value. ②The material agency of marine space determines the feasibility of the capitalization of marine space and is also the decisive subject in shaping the specific practice of capitalization. The survival and profit needs of mariculture fishermen and enterprises drive the realization of the capitalization of marine space. China's central and local governments participate in realizing the capitalization of marine space with the relevant institutional policies and norms aimed at economic development.